(untitled) (Patan Prospective Journal, 2024)
This article critically analyzes the practices of teaching and learning English in schools and colleges in Nepal. By using the theory of representation, the research is accomplished. I have used secondary sources of materials including research articles, research reports, dissertations on the practices of English as a medium of instruction in schools and colleges of Nepal. This paper analyzes the probable opportunities and challenges as seen in the homogenous education practices in Nepal. It relates education with opportunities and highlights challenges as the implications of the teaching and learning English in Nepal. The paper encompasses the causes and effects of using English as a medium of instruction in all levels of education. Why parents, education entrepreneurs, teachers, and students prefer English to Nepali and other national languages as the medium of instruction is the core question to be answered in this research paper. The finding is the employment opportunity in the global spectrum and the language of power that alleviates the social status of the speakers of English people including guardians, school principals, and teachers choose English as the medium of teaching and learning in both private and public academic institutions. Despite numerous challenges, most of the Nepalese prefer to learn English and take it as a means of communication and knowledge attainment. By using the qualitative research design especially text analysis as the method, the paper is accomplished.